Analysis Of Accountability And Transparency Of Digital Zakat Management In Amil Zakat Institutions: A Sharia Accounting Perspective: ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ZAKAT DIGITAL PADA LEMBAGA AMIL ZAKAT : PERSPEKTIF AKUNTANSI SYARIAH - Khulataini, Luluk (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract. This study aims to examine the Amil Zakat Institution's digital zakat management's transparency and accountability from a Sharia accounting standpoint. Regarding this study, it employs a literature review methodology in conjunction with qualitative research techniques. Digital transformation in the practice of zakat encourages changes in the pattern of management of zakat funds, thus requiring zakat institutions to maintain the principles of responsibility and transparency in every process. This study is conducted by reviewing various relevant sources to understand the principles and laws of Sharia accounting in the handling of digital zakat. This research indicates that the implementation of accountability and transparency of digital zakat can be improved through digital audit trail and information access. Although the digital system process facilitates the collection and reporting of zakat funds, not all zakat institutions have adequate information systems to ensure sustainable accountability and transparency. In addition, there is a need for improvement in terms of digital security and compliance with Sharia accounting. In the perspective of Sharia accounting, in addition to technical compliance, zakat management must also reflect the values of trustworthiness, clear reporting, and social responsibility to Muzakki and Mustahik. Therefore, it may be said that the Amil Zakat Institution can maximize zakat management in an accountable and transparent manner by adopting a digital system that complies with Sharia accounting principles.   Abstrak. Studi ini bertujuan untuk mendeskripsikan transparansi dan akuntabilitas dalam manajemen zakat digital Lembaga Amil Zakat dari perspektif Akuntansi Syariah. Adapun studi ini dilakukan dengan menggunakan pendekatan kualitatif yang melibatkan peninjauan literatur. Transformasi digital dalam praktik zakat mendorong perubahan pada pola pengelolaan dana zakat, sehingga menuntut Lembaga zakat untuk tetap menjaga prinsip tanggung jawab dan keterbukaan pada setiap prosesnya. Kajian ini dilakukan dengan menelaah berbagai sumber yang relevan untuk memahami prinsip dan hukum akuntansi Syariah dalam pengelolaan zakat digital. Dari kajian ini mengindikasikan adanya implementasi akuntabilitas dan transparansi zakat digital dapat ditingkatkan melalui jejak audit digital dan akses informasi. Meskipun proses sistem digital mempermudah dalam penghimpunan serta pelaporan dana zakat, tidak semua Lembaga zakat memiliki sistem informasi yag memadai untuk menjamin akuntabilitas dan transparansi yang berkelanjutan. Selain itu, perlu adanya peningkatan dalam hal keamanan digital dan kepatuhan terhadap akuntansi Syariah. Dalam perspektif akuntansi Syariah, pengelolaan zakat selain harus sesuai teknis juga harus mencerminkan nilai-nilai amanah, pelaporan yang jelas, dan tanggung jawab sosial kepada Muzaki dan Mustahik. Dapat disimpulkan bahwa pengoptimalan pengelolaan dana zakat secara akuntabel dan transparan dapat dilakukan oleh Lembaga Amil Zakat melalui pengaplikasian sistem digital sejalan dengan ketentuan dan peraturan akuntansi syariah yang sah.